Psf2, a member of the heterotetrameric GINS Complex, plays a role in cell cycle progression and maintenance of genomic integrity - Henderson, Laura M. (East Carolina University, 2010)
Multiple proteins are involved in the complete and accurate replication of the genome during S phase of the cell cycle. At the G1/S phase transition, the heterotetrameric GINS complex is recruited to the origin, and facilitates the helicase activity of the Mcm2-7 complex. Each of the four subunits of the GINS complex is essential for proper completion of DNA replication initiation and elongation. Inaccurate replication of the genome results in a multitude of disease states, specifically, cancer.  Psf2, a subunit of the GINS complex, has been previously implicated in the segregation of chromosomes during M phase. Additionally, it has been shown that reduced levels of Psf2 in yeast results in stalled replication forks and incomplete DNA replication. However, to date, the function of Psf2 in higher eukaryotes has only been studied in tissue culture models. To provide insight into the role of Psf2 in a multicellular organism, we used an in vivo approach to characterize the phenotypes resulting from the C-terminal truncation of Psf2 in a homozygous lethal mutant in Drosophila. Through analysis of larval brain tissue, salivary tissue, ovarioles, and embryonic tissue, we found the mutant Psf2 displays defects during M phase of the cell cycle and DNA replication in endoreplicating cells. Curiously, the RNAi knockdown of Psf2 results in a defect in S phase of the cell cycle, with no effects on M phase. Therefore, we hypothesize that Psf2 plays an essential role in cell cycle progression. Additionally, removal of the C-terminal domain is essential for either the correct formation of the GINS complex, or for an external interaction, possibly with checkpoint or chromosome segregation proteins.
Keywords: Biology, Molecular; Biology, Cell; Cell Biology; Molecular biology; Genomics; Genomes; Proteins; DNA replication--Regulation; Cell cycle--Regulation; Eukaryotic cells